Genetic variability of Plasmodium vivax and patterns of recurrence in asymptomatic malaria at Mazan, Iquitos, Peru - Valencia Ayala, Edward (2012)
Plasmodium vivax displays a high genetic variability for recurrent episodes of illness. Objectives: To determine the genetic variability of P. vivax and patterns of recurrence in asymptomatic malaria. Design: Descriptive analytical. Setting: Laboratory of Infectious Disease Research, Universidad Peruana Cayetano Heredia. Population: Individuals from Mazan, Iquitos, Peru, a malaria endemic region. Intervention: Between June 2006 and November 2008, 222 individuals were analyzed with two sequential blood samples. Main outcome measures: Identification of P. vivax, genotyping based on gene pvmsp3-α, genetic variability of P. vivax and patterns of recurrence. Results: First evaluation: Positive for P. vivax 191/222 (86%), P. falciparum 2/222 (0.9%), mixed infection 21/222 (9.5%) and negative 8/222 (3.6%). Second evaluation: 180/191 (94.2%) remained positive for P. vivax. Genotyping by nested PCR and enzymatic digestion showed polyclonal haplotypes in 17/180 (9.4%) and monoclonal in 163/180 (90.6%). Different haplotypes (reinfection) were observed in 88/180 (48.9%) and identical haplotypes (relapse) in 75/180 (41.7%). Conclusions: There was P. vivax high genetic variability and patterns of malaria recurrence based on genotyping showed differences between reinfection and relapse in asymptomatic individuals in Mazan, Iquitos.